Presence of Comorbidities Associated with Severe Coronavirus Infection in Patients with Inflammatory Bowel Disease - Parekh, Rajen (Dig Dis Sci, 2021)
BACKGROUND: Comorbidities increase the risk of coronavirus disease 2019 (COVID-19) hospitalization and mortality. As many comorbidities are common in patients with inflammatory bowel diseases (IBD), we sought to investigate the effects of comorbidities in these patients on infection severity. AIM: To evaluate association between individual comorbidities and COVID-19 infection severity among patients with IBD. METHODS: Data were obtained from SECURE-IBD, an international registry created to evaluate COVID-19 outcomes in patients with IBD. We used multivariable regression to analyze associations between eleven non-IBD comorbidities and a composite primary outcome of COVID-19-related hospitalization or death. Comorbidities were first modeled individually, adjusting for potential confounders. Next, to determine the independent effect of comorbidities, we fit a model including all comorbidities as covariates. RESULTS: We analyzed 2,035 patients from 58 countries (mean age 42.7 years, 50.6% male). A total of 538 patients (26.4%) experienced severe COVID-19. All comorbidities but a history of stroke and obesity were associated with severe infection in our initial analysis, with adjusted odds ratios ranging from 1.9 to 3.7. In a model including all comorbidities significantly associated with the composite outcome in the initial analysis, as well as other confounders, most comorbidities remained significant, with the highest risk in chronic kidney disease and chronic obstructive pulmonary disease. CONCLUSION: Many non-IBD comorbidities are associated with a two to threefold increased risk of COVID-19 hospitalization or death among patients with IBD. These data can be used to risk-stratify and guide treatment and lifestyle decisions during the ongoing pandemic.